2000
DOI: 10.1038/82741
|View full text |Cite
|
Sign up to set email alerts
|

Caspase inhibitors improve survival in sepsis: a critical role of the lymphocyte

Abstract: Sepsis induces lymphocyte apoptosis and prevention of lymphocyte death may improve the chances of surviving this disorder. We compared the efficacy of a selective caspase-3 inhibitor to a polycaspase inhibitor and to caspase-3-/- mice. Both inhibitors prevented lymphocyte apoptosis and improved survival. Caspase-3-/- mice shared a decreased, but not total, block of apoptosis. The polycaspase inhibitor caused a very substantial decrease in bacteremia. Caspase inhibitors did not benefit RAG-1-/- mice, which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
463
5
11

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(502 citation statements)
references
References 29 publications
23
463
5
11
Order By: Relevance
“…In this respect Hotchkiss et al [52] observed early on that when administered one hour after experimental sepsis, the pan-caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp(O-methyl) fluoromethyl ketone (z-VAD) significantly reduced apoptosis in the thymus and spleen, and z-VAD administration (6mg/kg) immediately following and 24 hours after sepsis resulted in 100% survival as compared to 40% observed in controls. Inhibition of caspase-3 by injection of M-791 also markedly improved survival in septic mice, reducing thymocyte and splenocyte apoptosis [53] while the adoptive transfer of apoptosis-resistant T cells also markedly enhanced the survival rate of the septic animals [53]. Studies with C3H/HeJ (endotoxin-tolerant) and C3H/HeJ-FasL gld (endotoxin-tolerant/FasL-deficient) mice showed that the Fas/FasL pathway was a mediator of apoptosis in B220 + B cells of the Peyer's patches as well as CD4 + and CD8 + T cells of the intestinal intraepithelial lymphocyte (IEL) population or splenic CD4 + T cells during sepsis [19][20][21].…”
Section: Inhibiting Apoptosis Improves Septic Survival -Therapeutic Omentioning
confidence: 90%
“…In this respect Hotchkiss et al [52] observed early on that when administered one hour after experimental sepsis, the pan-caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp(O-methyl) fluoromethyl ketone (z-VAD) significantly reduced apoptosis in the thymus and spleen, and z-VAD administration (6mg/kg) immediately following and 24 hours after sepsis resulted in 100% survival as compared to 40% observed in controls. Inhibition of caspase-3 by injection of M-791 also markedly improved survival in septic mice, reducing thymocyte and splenocyte apoptosis [53] while the adoptive transfer of apoptosis-resistant T cells also markedly enhanced the survival rate of the septic animals [53]. Studies with C3H/HeJ (endotoxin-tolerant) and C3H/HeJ-FasL gld (endotoxin-tolerant/FasL-deficient) mice showed that the Fas/FasL pathway was a mediator of apoptosis in B220 + B cells of the Peyer's patches as well as CD4 + and CD8 + T cells of the intestinal intraepithelial lymphocyte (IEL) population or splenic CD4 + T cells during sepsis [19][20][21].…”
Section: Inhibiting Apoptosis Improves Septic Survival -Therapeutic Omentioning
confidence: 90%
“…58 In heart failure, cardiomyocytes show autophagic rather than apoptotic cell death. 59 One of the few diseases in which caspase inhibitors may yield convincing preclinical effects is septic shock, 60 which involves the contribution of caspases, not only as cellular demolition enzymes but also for the biosynthesis of proinflammatory cytokines. Thus, although caspase inhibition can successfully prevent the phenotypic manifestation of apoptosis, it often does not prevent cell death, which is likely to be executed through different mechanisms (including apoptosis-like cell death, autophagy and necrosis) 5,23,24,34,61 and perhaps through phagocytic recognition and destruction.…”
Section: Comments and Examplesmentioning
confidence: 99%
“…Caspase inhibitors have also shown some benefit in murine models of sepsis (Ref. 150). However, the targeted blockade of apoptosis to lymphocytes, and not to cell populations that harbour EBOV, is a formidable hurdle that must be overcome before this therapeutic strategy can be fully realised.…”
Section: Inhibition Of Apoptosis Of Bystander Lymphocytesmentioning
confidence: 99%